Noncanonical Transforming Growth Factor β (TGFβ) Signaling in Cranial Neural Crest Cells Causes Tongue Muscle Developmental Defects - Iwata, Jun-ichi (American Society for Biochemistry and Molecular Biology, 2013)
Microglossia is a congenital birth defect in humans and adversely impacts quality of life. In vertebrates, tongue muscle derives from the cranial mesoderm, whereas tendons and connective tissues in the craniofacial region originate from cranial neural crest (CNC) cells. Loss of transforming growth factor β (TGFβ) type II receptor in CNC cells in mice (Tgfbr2(fl/fl);Wnt1-Cre) causes microglossia due to a failure of cell-cell communication between cranial mesoderm and CNC cells during tongue development. However, it is still unclear how TGFβ signaling in CNC cells regulates the fate of mesoderm-derived myoblasts during tongue development. Here we show that activation of the cytoplasmic and nuclear tyrosine kinase 1 (ABL1) cascade in Tgfbr2(fl/fl);Wnt1-Cre mice results in a failure of CNC-derived cell differentiation followed by a disruption of TGFβ-mediated induction of growth factors and reduction of myogenic cell proliferation and differentiation activities. Among the affected growth factors, the addition of fibroblast growth factor 4 (FGF4) and neutralizing antibody for follistatin (FST; an antagonist of bone morphogenetic protein (BMP)) could most efficiently restore cell proliferation, differentiation, and organization of muscle cells in the tongue of Tgfbr2(fl/fl);Wnt1-Cre mice. Thus, our data indicate that CNC-derived fibroblasts regulate the fate of mesoderm-derived myoblasts through TGFβ-mediated regulation of FGF and BMP signaling during tongue development.